Strategies for exiting the lockdown - McCoy, David (Henry Stewart Talks, 2020)
Conditions required for exiting the lockdown, Comparison of lockdown measures with Scandinavian countries, Strategies for exiting the lockdown, Possible outcomes from lifting the lockdown, Future of the pandemic in the USA and Russia